Macroeconomic conditions of pay in Polish economy in 1990-2007 - Nyk, Mariusz (Comparative Economic Research. Central and Eastern Europe, 2010)
Remuneration is a crucial element of economic processes. What it means is that the processes of production, distribution, exchange and consumption are not possible without a well planned pay strategy. There are many factors which influence salaries. The aim of this survey is to present salary stimulants of macroeconomic character. Those include GDP, inflation rate, unemployment rate, cost of work, protective package (unemployment benefit), efficiency, legislation protecting employees’ rights and legislation regulating employment relations. Each of these macroeconomic issues determine the level of salaries to a different extent. While analysing relations between those stimulants we should not jump to wrong conclusions explaining salary levels.